A STUDY OF STUDENTS LEARNING MODALITIES AT ENGLISH EDUCATION PROGRAM AT MUHAMMADIYAH UNIVERSITY OF BENGKULU - Tya Joice Angelia; Epi Wadison (Teaching English and Language Learning English Journal, 2023)
The objective of this research was to find students learning modalities in learning English at English education program. Design of the research in this research, the researcher used descriptive qualitative method and the research includes collecting and analysis of non-numeric data to understand concept and experiences. Subject of the research was students of the English education program. Researchers conducted research in semesters 3rd and 5th of the 2022/2023 academic year. Semester 3th consists of 29 students and semester 5th consists of 18 students, so the entire subject numbered 47 students. The research instrument is a questionnaire. The questionnaire was adapted from (Ldpride, 2021). The finding of this research showed that learning modalities in the 3rd semester was kinesthetic with percentage 44%. While in the 5th semester learning modalities was kinesthetic with percentage 36%. And learning modalities in the 3rd and 5th semesters are kinesthetic with a percentage 36%. It was suggested that the importance of knowing the appropriate learning modalities for the way they carry out learning activities will have a positive impact, such as being able to make it easier for students to absorb information so as to increase their interest and learning achievement. Keywords: Learning Modalities, English Education Program